Exploration of factors affecting hemodynamic stability following pheochromocytoma resection - cohort study - Liu, Lidan; Shang, Lihua; Zhuang, Yimeng; Su, Xiaojing; Li, Xue; Sun, Yumeng; Long, Bo (Frontiers in Endocrinology, 2024)
Purpose: Surgery is the only way to cure pheochromocytoma; however, postoperative hemodynamic instability is one of the main causes of serious complications and even death. This study's findings provide some guidance for improved clinical management.Patients and methods: this study was to investigate the factors leading to postoperative hemodynamic instability in the postoperative pathology indicated pheochromocytoma from May 2016 to May 2022.They were divided into two groups according to whether vasoactive drugs were used for a median number of days or more postoperatively. The factors affecting the postoperative hemodynamics in the perioperative period (preoperative, intraoperative, and postoperative) were then evaluated. Results: The median number of days requiring vasoactive drug support postoperatively was three in 234 patients, while 118 (50.4%) patients required vasoactive drug support for three days or more postoperatively. The results of the multivariate analysis indicated more preoperative colloid use (odds ratio [OR]=1.834, confidence interval [CI]:1.265-2.659, P=0.001), intraoperative use of vasoactive drug (OR=4.174, CI:1.882-9.258, P<0.001), and more postoperative crystalloid solution input per unit of body weight per day (ml/kg/d) (OR=1.087, CI:1.062-1.112, P<0.001) were risk factors for predicting postoperative hemodynamic instability. The optimal cutoff point of postoperative crystalloid use were 42.37 ml/kg/d. Conclusions: Hemodynamic instability is a key issue for consideration in the perioperative period of pheochromocytoma. The amount of preoperative colloid use, the need for intraoperative vasoactive drugs, and postoperative crystalloid solution are risk factors for predicting postoperative hemodynamic instability (registration number: ChiCT2300071166).